Digital Copyright Protection and Tracking System: A Web Based Platform for Invisible Watermarking and Ownership with Blockchain - Vinitha G; Vigneshwaran H; Rajesh Kumar S; Nithish A; Aswin Raj A (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The exponential rise of digital content has ushered in both unprecedented creative opportunities and significant threats to intellectual property. Traditional copyright enforcement mechanisms are increasingly challenged by decentralized content distribution and sophisticated piracy methods. This paper proposes a blockchain-integrated, end-to-end copyright protection and tracking system. The architecture combines a React (Vite) frontend with MetaMask-based Ethereum login, a Golang- powered API for file routing and orchestration, a VPS for secure file storage, and a Python-based watermarking engine for tamper-proof identification. Two key modules—digital copyright protection and access tracking—work together to embed invisible identifiers into uploaded content and monitor usage across a decentralized network. Through robust system design and strategic component integration, the solution ensures secure, scalable, and transparent enforcement of content ownership in modern digital ecosystems.
Keywords: Digital Copyright; Blockchain; Watermarking; MetaMask; File Tracking; Golang; Python; React; VPS; Ethereum